A Comparison of Physical Activity and Sedentary Lifestyle of University Employees through ActiGraph and IPAQ-LF. Issue 1 (7th February 2022) - Safi, Ayazullah; Cole, Matthew; Kelly, Adam; Deb, Sanjoy; Walker, Natalie
Introduction: The benefits of participating in physical activity (PA) are wide-ranging, such as lowering the risk of diabetes and anxiety. Employees' engagement in PA can also benefit their employers due to the potential reduction in absenteeism and increased productivity. However, the PA levels and sedentary behaviour of university employees are yet to be examined using a mixed methods approach. This study aimed to monitor the PA and sedentary lifestyle (SL) of university employees' objectively and subjectively for a whole week. Methods: Sixty-four employees (male = 33; female = 31) wore a PA monitor for a whole week and simultaneously completed the International Physical Activity Questionnaire Long Form (IPAQ-LF) to evaluate light, moderate to vigorous physical activity (MVPA), and SL amongst employees from different job roles such as Academics, Administration, and Professionals Service. Results: The ActiGraph results determined that employees engaged in significantly more light PA, and MVPA compared to the self-reported IPAQ-LF (p < 0.05). There were no significant differences in SL between ActiGraph and IPAQ-LF (p > 0.05). However, there were significant differences across gender light PA Z = –6.139, p = .001, MVPA Z = –4.962, p = .001 but no significant differences in SL Z = –.869, p = .385. Also, there were significant differences across job roles light PA, MVPA (p < 0.05) but no significant differences in SL across job roles between both tools (p > 0.05). Discussion and conclusion: Findings suggest, IPAQ-LF presented lower light PA, MVPA, and SL than ActiGraph. Thus, considering the impact of prolonged SL on health and wellbeing, future research is needed to explore the challenges this population faces regarding PA engagement and propose potential interventions to reduce SL amongst university employees.